The real ghost in the machine. - Erwig, Martin (World Today)
The article offers information on the relationship between algorithms and computation. Topics discussed include need to master a programming language for the amplification of modern technology; runtime of a quadratic algorithm grows with the square of the input size; and Ben Shneiderman, University of Maryland argued to make National Algorithm Safety Board who hold algorithms accountable and provide transparency to the public.